Genistein, a Natural Isoflavone, Alleviates Seizure-Induced Respiratory Arrest in DBA/1 Mice - Guo, Jialing; Min, Daniel; Feng, Hua-Jun (Frontiers in Neurology, 2021)
Objective: Sudden unexpected death in epilepsy (SUDEP) is a fatal event that ranks second in years of potential life lost among neurological disorders. Seizure-induced respiratory arrest (S-IRA) is the primary instigator leading to death in many SUDEP cases. However, there are currently no effective preventive strategies against S-IRA other than the seizure control. Therefore, it is critical to develop new avenues to prevent SUDEP by investigating the pharmacological interventions of S-IRA. In the present study, we examined the effect of genistein, an isoflavone found in various dietary vegetables, on the incidence of S-IRA in DBA/1 mice. Methods: DBA/1 mice exhibited generalized seizures and S-IRA when subjected to acoustic stimulation. Genistein was intraperitoneally administered alone or in combination with an adrenoceptor antagonist and a serotonin (5-HT) receptor antagonist, respectively. The effects of drug treatments on S-IRA incidence and seizure behaviors were examined. Results: The incidence of S-IRA in DBA/1 mice was significantly reduced 2 hr after injection of genistein at 1-90 mg/kg as compared with that in the vehicle control. Genistein could block S-IRA without interfering with any component of seizures, especially at relatively lower dosages. The S-IRA-suppressing effect of genistein was reversed by an alpha2 adrenoceptor antagonist but was not altered by an alpha1 antagonist. The inhibitory effect of genistein on S-IRA was not affected by a 5-HT3 or 5-HT2A receptor antagonist. Significance: Our data show that genistein reduces S-IRA incidence and can specifically block S-IRA in DBA/1 mice. Its suppressing effect on S-IRA is dependent on activating alpha2 adrenoceptors. Our study suggests that genistein, a dietary supplement, is potentially useful to prevent SUDEP in at-risk patients.